THE EFFECT OF GOOD CORPORATE GOVERNANCE MODERATED CORPORATE SOCIAL RESPONSIBILTY DISCLOSURE ON THE FINANCIAL PERFORMANCE OF BANKING COMPANIES - Pahrizal Sofyan; Hedwigis Esti Riwayati; Edy Sukarno (Dinasti International Journal of Education Management And Social Science, 2022)
Research about effectiveness of Good Corporate Governance with Corporate Social Responsibility on financial performance in banking companies is very necessary because the characteristics of banking companies are different from other industries. This research aims to analyze the effect of Good Corporate Governance to bank financial performance as measured by Return on Asset and Corporate Social Responsibility disclosure as moderation variable. The determination of samples is using purposive sampling method, which is a sampling technique using certain considerations and limitations so that the selected sample is relevant to the purpose of the study. The sample used in this study was 4 (four) State-Ownedbanking companies and participants in the Corporate Governance Perception Index from 2012-2020 with disclosure of aspects of Corporate Social Responsibility as measured by the Category of Global Reporting Initiative. Researchers used regression and moderating analysis techniques as well as the Eviews 12.0 application to test the study data. The results showed that Good Corporate Governance has a significant negative effect to Return on Asset and Corporate Social Responsibility strengthens the relationship of Good Corporate Governance to Return on Asset.